MENAKSIR MERAUKE SEBAGAI KOTA YANG SEDANG BERKEMBANG - Wayrohi Meilvidiri; Rizka Jafar (Musamus Journal of Economics Development, 2019)
This study is to answer whether the city of Merauke is developing or not by using the prerequisite concept of agriculture surplus, urban production and transportation to exchange. The Data used is the value of agricultural, industrial and electrical energy production; and motor vehicles. Population and population density data, the county capital mileage to the district capital, and road conditions as supporting data. Qualitative descriptive is used to describe, and analyze the data to draw conclusions based on the concepts and facts found. Findings of this study that the first prerequisite, agriculture surplus is fulfilled, while the second prerequisite, urban production, not fulfilled, the third requirement of transportation to exchange is also not fulfilled. It can be said that the city of Merauke using these three verses can not be said as a thriving city. Keywords: agriculture surplus, urban production, transportation to exchange